Integration of the Design Thinking Methodology in the Classic Design of Pedestrian Crossings in Peru - Rivera Huaman, Ricardo Franco (2024)
Urban road designs often exhibit accessibility deficiencies, with one of the causes being the failure to consider user opinions in public urban designs. The document at hand presents the results of applying the Design Thinking methodology, which incorporates user opinions, to the design of pedestrian crossings at an intersection in Lima. It describes the various stages of the innovative process, from identifying design limitations to evaluating the implementation of the proposed design. The document also underscores the significance of survey results obtained from pedestrians, as they provided valuable feedback on the developed design. The ultimate beneficiaries of the design will be the users who traverse the study area. In conclusion, the research work contributed to the application of Design Thinking in the classic civil engineering design process and highlights the importance of considering the pedestrian in the design of pedestrian crossings to guarantee a comprehensive design that improves pedestrian accessibility.